Breech delivery: changing scenario - Wanjari, Sanjivani Anil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: In context of the debate surrounding the optimal mode of delivery for the breech, we did a retrospective study in our hospital. The aim of the study was to assess the mode of delivery, to analyze the indications for caesarean section and to find out the perinatal outcome in breech during the study period. Methods: A retrospective study was done of women with breech admitted to our unit at Daga hospital Nagpur. All women having viable breech pregnancies of more than 34 weeks gestation were included in the study. An effort was done to find out whether mode of delivery affected neonatal outcome. Results: Although it is not our policy to have an elective planned caesarean section for all breech presentations, there was a high rate of caesarean section for breech. Most of the caesarean sections were in primigravida having a breech presentation (58.62%). Nearly 92 % of women in the study group were in the age group of 20 to 30 years. A high caesarean section rate in a young population can have implications in future pregnancies. Conclusions: There is an on-going debate about the best way to deliver breeches. The policy of planned caesarean section for breech may not be feasible in all hospitals and by choice or default, vaginal breech births will continue to take place, which means attention is still warranted to skills and techniques that may improve outcomes for the baby.